Basic Concepts and Indications of CAR T Cells - van den Berg, Jana; Läubli, Heinz; Khanna, Nina; Jeker, Lukas T.; Holbro, Andreas (Hämostaseologie, 2025)
Chimeric antigen receptor (CAR) T cell therapy has revolutionized cancer immunotherapy, particularly for hematological malignancies. This personalized approach is based on genetically engineering T cells derived from the patient to target antigens expressed—among others—on malignant cells. Nowadays they offer new hope where conventional therapies, such as chemotherapy and radiation, have often failed. Since the first FDA approval in 2017, CAR T cell therapy has rapidly expanded, proving highly effective against previously refractory diseases with otherwise a dismal outcome. Despite its promise, CAR T cell therapy continues to face significant challenges, including complex manufacturing, the management of toxicities, resistance mechanisms that impact long-term efficacy, and limited access as well as high costs, which continue to shape ongoing research and clinical applications. This review aims to provide an overview of CAR T cell therapy, including its fundamental concepts, clinical applications, current challenges, and future directions in hematological malignancies.
Keywords: chimeric antigen receptor T cell therapy; adoptive cellular therapy; immunotherapy; lymphoma; leukemia